Photoelectric wafer defect detection method
Through the coupled growth of quantum dots and wafer defects, the high fluorescence efficiency and deep labeling capabilities of quantum dots are used to solve the limitations of traditional wafer detection methods in terms of resolution, speed and cost, and achieve efficient and accurate detection of photoelectric wafer defects.
Patent Information
- Application Number
- CN202411726865.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional wafer detection methods have significant limitations in resolution, detection speed and cost, and it is difficult to effectively detect micro-nano damage and defects of photoelectric wafers.
Through the coupled growth of quantum dots and wafer defects, the high fluorescence efficiency and deep labeling capabilities of quantum dots are used to achieve efficient labeling and detection of photoelectric wafer surface defects.
Accurate detection of micro- and nano-scale defects is achieved, which improves the adaptability and flexibility of detection technology, reduces detection cost and time, and improves detection accuracy.
Smart Images

Figure CN119650451A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductors, and in particular relates to a method for detecting defects in photoelectric wafers. Background Art
[0002] Optoelectronic wafers are the basis of semiconductor chip manufacturing, and their quality directly affects the performance and reliability of the final chip. The wafer manufacturing process is generally divided into cutting, grinding, lapping, polishing, etc. Each process is prone to produce different types of surface and subsurface defects, such as scratches, microcracks, residual stress, particle contamination, etc. These defects will not only directly affect the mechanical strength and optoelectronic properties of the wafer, but may also cause further damage and failure in subsequent processes, thereby having varying degrees of negative impact on the overall performance and stability of the optical chip.
[0003] Specifically, during the wafer cutting process, the wafer may produce tiny cracks and fragments due to the wear of the cutting tool or improper operation; during the wafer grinding and lapping process, mechanical stress and abrasive particles may cause increased surface roughness and subsurface damage; during the wafer polishing process, although the surface appears smooth, there may still be microscopic defects and chemical residues. The presence of these defects will not only reduce the optical properties of the chip, such as transmittance and optical uniformity, but also lead to failure or unstable performance of the prepared device. As an emerging nanomaterial technology, quantum dot technology is gradually attracting widespread attention due to its unique quantum confinement effect and excellent optoelectronic properties. Quantum dots have the advantages of small size, adjustable band width, and high luminescence efficiency. They are widely used in optoelectronic devices, photovoltaic cells, display technology, and bioimaging. However, in practical applications, the performance of quantum dots is highly dependent on the quality of their coupling growth with the substrate material. In the traditional process, quantum dots are directly coated on the wafer surface. In this way, the coupling strength between quantum dot materials and wafer micro-nano damage is low, there are many grain boundary defects, and the film uniformity is poor, which leads to the need to improve the sensitivity of micro-nano damage detection. In addition, there are problems such as low air stability and water stability, single quantum dot solvent, and poor substrate adaptability. Therefore, it is key to study the coupling growth mechanism of quantum dots and wafer defects and develop effective wafer detection technology.
[0004] At present, traditional wafer inspection methods are divided into two types: one is destructive inspection methods. Among them, destructive inspection methods mainly include chemical etching, magnetorheological polishing inspection method, angle polishing method, etc. (1) Chemical etching method. The test element is layered and etched according to a specially prepared NH4F and HF mixed etching solution to obtain the depth and morphology of the etching step, and the depth of the sub-surface defect layer is determined based on the difference in etching rate or the change in morphological characteristics. The advantages of this method are simple operation and low cost; the disadvantages are that it is easily disturbed by environmental factors and has low accuracy. (2) Magnetorheological polishing inspection method. The magnetorheological polishing method uses magnetorheological polishing liquid (a suspension formed by mixing base liquid, magnetic particles and stabilizer) for inspection. In the absence of a magnetic field, the magnetorheological polishing liquid can flow, but in a strong magnetic field environment, the flow characteristics of the liquid will change dramatically, showing a property similar to that of a solid; but after the magnetic field environment disappears, the original flow characteristics are restored, and the reversible change of liquid-solid properties is achieved under the action of the magnetic field. The magnetorheological polishing observation method uses magnetic materials added to the polishing liquid to polish and corrode the sample, so that the sub-surface damage is exposed, and then the damage is observed under a microscope, and the polishing-observation steps are repeated until the damage disappears. The magnetorheological polishing observation method introduces almost no damage when preparing the sample, which can solve the disadvantage that the angle polishing method introduces new damage when preparing the sample. However, this method has a long working time, polishing takes up most of the time, and the detection efficiency is low. (3) Angle polishing method. Its detection principle is to use resin glue to glue the polishing sample and the sample to be tested, which can effectively prevent the expansion of the original damage during the angle polishing process. The angle polishing method is simple and convenient to operate, low in cost, and can directly obtain the sub-surface damage depth. However, new damage will be introduced when preparing the angle section, and cracks will also expand during the corrosion process of the angle section, causing the sub-surface crack depth value detected in the end to increase.
[0005] The other type is non-destructive testing. They mainly include total internal reflection microscopy, optical coherence tomography, confocal laser scanning microscopy, fluorescence microscopy, etc. (1) Total internal reflection microscopy is based on the principle of total internal reflection of light to perform dark field scattering microscopy imaging of defects in optical components. However, the detection accuracy of this method is not high, and it has strict requirements on the quality and angle of the light beam. (2) Optical coherence tomography. It mainly consists of three parts, including a broadband light source, an interferometer, and a photodetector. The photodetector is used to receive the interference light, and then the interference pattern is processed to obtain an optical coherence tomography image, thereby obtaining an interference spectrum carrying the depth information of the sample. After Fourier transformation, the depth information of the sample can be extracted. Due to the random distribution of subsurface defects in optical components, it is difficult to obtain an interference image of the defect area, and the equipment and optical path of this method are relatively complex and costly. (3) Confocal laser scanning microscopy. By building a microscopic imaging system, imaging of different focus sections can be achieved, thereby achieving optical section imaging of different depths of the sample. The main disadvantage of this method is that the field of view is very small, it is difficult to locate the defect area, and the amount of image data obtained by scanning is huge, requiring complex post-reconstruction algorithms. (4) Fluorescence microscopy. Fluorescent dyes are used to mark defects in optical wafers. The experimental phenomenon of this method is obvious, the detection accuracy is high, and the speed is fast. However, due to the surface tension of the material, the fluorescent dye cannot wet the crack tip.
[0006] In summary, although traditional wafer inspection methods can meet the detection needs of optical wafer surface defects to a certain extent, they have significant limitations in terms of resolution, inspection speed, cost, etc. Summary of the invention
[0007] The purpose of the present invention is to provide a method for detecting defects in optoelectronic wafers. The present invention realizes the detection of wafer defects by coupling the growth of quantum dots and wafer defects. The present invention aims to reveal the coupling growth mechanism of quantum dots and wafer defects, break through the problem that traditional fluorescent dyes cannot penetrate deep into wafer defects, and use the advantages of high fluorescence efficiency and small size of quantum dots to achieve efficient marking of defects on the surface of optoelectronic wafers, and further improve the adaptability and flexibility of detection technology to meet the growth requirements of various types of optoelectronic wafers. And develop low-cost, high-speed wafer defect detection technology to achieve efficient and accurate wafer defect detection.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for detecting defects in an optoelectronic wafer comprises the following steps:
[0010] The quantum dot precursor solution is coated on the surface of the optoelectronic wafer and annealed. After the quantum dot film is formed, it is irradiated under ultraviolet light. The displayed fluorescent signal can mark the defects on the surface of the optoelectronic wafer, thereby achieving the purpose of detecting defects in the optoelectronic wafer.
[0011] Preferably, the quantum dots include but are not limited to CsPbBr3 quantum dots, FAPbI3 quantum dots, CsPbI3 quantum dots or Cs3Cu2I5 quantum dots.
[0012] Preferably, the material of the optoelectronic wafer includes but is not limited to sapphire, silicon carbide, silicon dioxide, fused quartz, gallium nitride, gallium arsenide or single crystal silicon.
[0013] Compared with traditional fluorescent labeling solutions, the quantum dot solution used in the present invention has the ability to infiltrate nanoscale defects and form a mark with a depth ratio of up to 1:3. This deep labeling capability helps to fully understand the internal structure and defect extension of wafer defects. Whether it is micron-scale or nanoscale defects, they can be marked by quantum dots to form clear and stable fluorescent signals.
[0014] In addition, the present invention has concluded through experiments that quantum dot solutions exhibit good coupling effects with wafers of different materials. Therefore, the use of quantum dots to detect wafer defects has excellent versatility.
[0015] Take CsPbBr3 quantum dots as an example (the structural diagram and photoluminescence spectrum of CsPbBr3 quantum dots are shown in Figure 1 , where (a) is a schematic diagram of the structure of CsPbBr3 quantum dots, and (b) is a photoluminescence spectrum of CsPbBr3 quantum dots). The quantum dots usually have a cubic crystal structure and are an inorganic perovskite quantum dot with excellent photoelectric properties. They have attracted much attention due to their wide applications in optoelectronic devices, display technology, photovoltaic cells, and other fields. CsPbBr3 quantum dots have high photoluminescence efficiency and a narrow luminescence bandwidth, and can emit pure green light.
[0016] First, a CsPbBr3 quantum dot precursor solution is prepared, and then the prepared CsPbBr3 quantum dot precursor solution is used to grow a CsPbBr3 quantum dot film on wafers of different materials to achieve the detection effect.
[0017] The steps for preparing the CsPbBr3 quantum dot precursor solution include:
[0018] In a glove box with a nitrogen environment, PMMA (polymethyl methacrylate) and a solvent are mixed and placed in a magnet. The mixed solution is placed on a heating plate, the temperature of the heating plate is set to 90-120°C, the speed is modulated to 1500-1800 rpm, and heated and stirred for 1-3 hours until a transparent solution is formed, i.e., a PMMA solution.
[0019] In a glove box with nitrogen atmosphere, take PbBr2 and CsBr powders in a glass bottle, add solvent to dissolve, and put in a magnet. Place the two solutions on a heating plate, set the heating temperature to 50-80°C, set the speed to 1000-1500rpm, and stir overnight. Then filter the two solutions through a 0.22μm syringe filter to obtain CsBr solution and PbBr2 solution respectively.
[0020] The solvent may be a polar solvent or a non-polar solvent. The polar solvent may be N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO), and the non-polar solvent may be n-hexane or chlorobenzene.
[0021] In a glove box with a nitrogen environment, the CsBr solution and PMMA solution obtained above were mixed, the mixed solution was placed on a heating plate, a magnet was placed, the temperature of the heating plate was adjusted to 90-120°C, the rotation speed was 1500-1800rpm, and the mixture was heated and stirred for 10-12h. The PbBr2 solution obtained in the above step was then added, the molar ratio of CsBr to PbBr2 was 0.9-1.1:0.9-1.1, and the mixture was heated and stirred at 90-120°C and 1500-1800rpm for 10-12h to obtain a CsPbBr3 quantum dot precursor solution.
[0022] The in-situ growth steps of CsPbBr3 quantum dots include:
[0023] After preheating the CsPbBr3 quantum dot precursor solution obtained in the above steps to 70-100°C, it is added dropwise to the cleaned wafer substrate. The optional substrate materials include but are not limited to sapphire (Al2O3), silicon carbide (SiC), silicon dioxide (SiO2) and single crystal silicon (Si). Use a coating machine to spin coat at a speed of 1000-2000rpm for 20-40 seconds to obtain a CsPbBr3 / PMMA wet film. The CsPbBr3 / PMMA wet film substrate obtained in the above steps is placed on a heating plate at 70-100°C to promote in-situ nucleation and crystallization (annealing) of CsPbBr3 perovskite quantum dots. The purpose of the annealing process is to promote further crystallization and growth of CsPbBr3 quantum dots, while enhancing the coupling strength between quantum dots and substrates. Anneal at 40-110°C for 1-5 minutes to obtain a CsPbBr3 / PMMA quantum dot composite film that is in-situ grown and coupled on the wafer.
[0024] The growth mechanism of CsPbBr3 quantum dots can be divided into the following key steps:
[0025] 1. Ionic state infiltration: In the solution, there is Cs + and Pb 2+ions. These ions are approximately nanometers in size, so they can easily enter extremely narrow defects on the surface of the wafer substrate and achieve full wetting at the microscopic scale. + and Pb 2+ It can efficiently fill tiny depressions and cracks on the substrate, providing good initial conditions for subsequent crystal growth.
[0026] 2. In-situ nucleation and crystallization: The ion-impregnated wafer is placed on a hot plate for annealing. The annealing process is usually carried out at a temperature of 50 to 100°C. During the heating process, Cs + and Pb 2+ The ions undergo further bonding reactions and gradually form CsPbBr3 nanocrystals. The heat energy provided by the hot plate promotes the movement and reaction rate of the ions, causing them to quickly combine into crystals. At this stage, CsPbBr3 nanocrystals begin to nucleate in situ inside and around the defects and gradually grow to form evenly distributed quantum dots.
[0027] 3. Nanocrystal growth and coupling: During the annealing process, as time goes by, CsPbBr3 nanocrystals gradually grow and form a stable quantum dot structure. These nanocrystals can be evenly distributed on the substrate surface and form a strong coupling with the substrate. Since CsPbBr3 nanocrystals have good size control and uniformity, their growth process can effectively avoid the problems of excessive aggregation and uneven size, ensuring good coverage and marking effects of quantum dots in defects.
[0028] In the technical solution of the present invention, whether the solvent used in the quantum dot precursor solution is polar or non-polar does not affect the display of the fluorescence signal.
[0029] The beneficial technical effects of the present invention are as follows:
[0030] Quantum dots have excellent fluorescence efficiency and stability, and can provide high-contrast marking effects in SEM images. This makes the detection of micron- and nano-scale defects more precise and the details clearer.
[0031] Traditional fluorescent labeling solutions have limited wetting ability in nanoscale defects and can only cover the surface. However, quantum dots can penetrate deep into the defects, forming a mark with a depth ratio of up to 1:3. This deep labeling capability helps to fully understand the internal structure and extension of the defect.
[0032] Quantum dots have excellent adaptability and versatility, showing good stability and coupling effects under different types of wafer conditions. Quantum dots can efficiently couple with various types of optical wafers, including sapphire, silicon carbide, silicon dioxide and silicon substrates, showing excellent versatility. Whether it is micron- or nano-scale defects, quantum dots can evenly cover and mark them to form clear and stable fluorescence signals. This excellent coupling performance makes it an ideal choice for optical wafer defect detection. Quantum dots not only show excellent growth performance on various wafer substrates, but also have significant flexibility in solution preparation and preservation, and can be stably preserved in polar and non-polar solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the structure and photoluminescence spectrum of CsPbBr3 quantum dots, where (a) is a schematic diagram of the structure of CsPbBr3 quantum dots, and (b) is a photoluminescence spectrum of CsPbBr3 quantum dots.
[0034] Figure 2 Schematic diagram of the process for preparing CsPbBr3 quantum dot precursor solution in Example 1-4.
[0035] Figure 3 These are pictures of the CsPbBr3 quantum dot precursor solution prepared in Example 1-4 under white light and 365nm ultraviolet light.
[0036] Figure 4 These are pictures of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the sapphire wafer in Example 5 under white light and 365nm ultraviolet light.
[0037] Figure 5 These are pictures of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the silicon wafer in Example 6 under white light and 365nm ultraviolet light.
[0038] Figure 6 These are pictures of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the silicon carbide wafer in Example 7 under white light and 365nm ultraviolet light.
[0039] Figure 7 These are pictures of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the silicon dioxide wafer in Example 8 under white light and 365nm ultraviolet light.
[0040] Figure 8These are SEM images of the coupling of CsPbBr3 quantum dots and silicon carbide wafers in Example 7, wherein (a) is the wetting effect of CsPbBr3 quantum dots in micron-scale defects, and (b) is the wetting effect of CsPbBr3 quantum dots in nanometer-scale defects.
[0041] Fig. 9 This is a diagram showing the effect of CsPbBr3 quantum dots on silicon dioxide wafer defect detection in Example 8.
[0042] Fig.10 These are pictures of the FAPbI3 / PMMA quantum dot composite film coupled by in-situ growth on the silicon dioxide wafer in Example 9 under white light and 365nm ultraviolet light.
[0043] Fig.11 These are pictures of the in-situ grown coupled CsPbI3 / PMMA quantum dot composite film on the silicon dioxide wafer in Example 10 under white light and 365nm ultraviolet light.
[0044] Fig.12 These are pictures of the in-situ grown coupled Cs3Cu2I5 / PMMA quantum dot composite film on the silicon dioxide wafer in Example 11 under white light and 245nm ultraviolet light. DETAILED DESCRIPTION
[0045] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0046] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0049] The schematic diagram of the process of preparing the CsPbBr3 quantum dot precursor solution in Example 1-4 of the present invention is shown in Figure 2 .
[0050] Example 1
[0051] Synthesis of CsPbBr3 / DMF Quantum Dot Solution
[0052] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of DMF were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 90°C, the speed was adjusted to 1600 rpm, and the mixture was heated and stirred for 1 h until a transparent solution was formed, i.e., PMMA / DMF solution.
[0053] (2) In a glove box with a nitrogen environment, take 1.267g (3.45mmol) of PbBr2 and 0.514g (2.41mmol) of CsBr powder into a 40mL glass bottle, add 5mL of DMF to each, and place a magnet. Place the two solutions on a heating plate, set the heating temperature to 50°C, the speed to 1300rpm, and stir overnight. Then filter the two solutions through a 0.22μm syringe filter to obtain CsBr / DMF solution and PbBr2 / DMF solution, respectively.
[0054] (3) Add 300 μL of the CsBr / DMF solution obtained in step (2) to 4 mL of the PMMA / DMF solution obtained in step (1), place the mixed solution on a heating plate, adjust the heating plate temperature to 90°C, the rotation speed to 1600 rpm, and heat and stir for 10 h. Then add 200 μL of the PbBr2 / DMF solution obtained in step (2), continue heating and stirring at 90°C and 1600 rpm for 10 h, and obtain a CsPbBr3 / DMF solution.
[0055] Example 2
[0056] Synthesis of CsPbBr3 / DMSO Quantum Dot Solution
[0057] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of DMSO were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 100°C, the speed was modulated to 1600 rpm, and heated and stirred for 2 h until a transparent solution was formed, i.e., PMMA / DMSO solution.
[0058] (2) In a glove box with a nitrogen environment, take 1.267g of PbBr2 and 0.514g of CsBr powder into a 40mL glass bottle, add 5mL of DMSO to each, and place a magnet. Place the two solutions on a heating plate, set the heating temperature to 60°C, set the speed to 1300rpm, and stir overnight. Then filter the two solutions through a 0.22μm syringe filter to obtain CsBr / DMSO solution and PbBr2 / DMSO solution, respectively.
[0059] (3) Add 300 μL of the CsBr / DMSO solution obtained in step (2) to 3 mL of the PMMA / DMSO solution obtained in step (1), place the mixed solution on a heating plate, adjust the heating plate temperature to 100°C, the rotation speed to 1600 rpm, and heat and stir for 10 hours. Then add 200 μL of the PbBr2 / DMSO solution obtained in step (2), continue heating and stirring at 100°C and 1600 rpm for 10 hours, and obtain a CsPbBr3 / DMSO solution.
[0060] Example 3
[0061] Synthesis of CsPbBr3 / n-hexane quantum dot solution
[0062] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of n-hexane were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 110°C, the speed was adjusted to 1600 rpm, and the mixture was heated and stirred for 1 h until a transparent solution was formed, i.e., the PMMA / n-hexane solution.
[0063] (2) In a glove box with a nitrogen environment, take 1.267g of PbBr2 and 0.514g of CsBr powder into a 40mL glass bottle, add 5mL of n-hexane to each, and place a magnet. Place the two solutions on a heating plate, set the heating temperature to 70°C, set the speed to 1300rpm, and stir overnight. Then filter the two solutions through a 0.22μm syringe filter to obtain CsBr / n-hexane solution and PbBr2 / n-hexane solution, respectively.
[0064] (3) Add 300 μL of the CsBr / n-hexane solution obtained in step (2) to 4 mL of the PMMA / n-hexane solution obtained in step (1), place the mixed solution on a heating plate, adjust the heating plate temperature to 110° C., rotate at 1600 rpm, and heat and stir for 10 h. Add 200 μL of the PbBr2 / n-hexane solution obtained in step (2), continue heating and stirring at 110° C. and 1600 rpm for 10 h, and obtain a CsPbBr3 / n-hexane solution.
[0065] Example 4
[0066] Synthesis of CsPbBr3 / Chlorobenzene Quantum Dots Solution
[0067] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of chlorobenzene were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 120°C, the speed was adjusted to 1600 rpm, and heated and stirred for 2 h until a transparent solution was formed, i.e., PMMA / chlorobenzene solution.
[0068] (2) In a glove box with a nitrogen environment, take 1.267g of PbBr2 and 0.514g of CsBr powder into a 40mL glass bottle, add 5mL of chlorobenzene to each, and put in a magnet. Place the above two solutions on a heating plate, set the heating temperature to 80°C, set the speed to 1300rpm, and stir overnight. Then filter the above two solutions through a 0.22μm syringe filter to obtain CsBr / n-hexane solution and PbBr2 / chlorobenzene solution, respectively.
[0069] (3) Add 300 μL of the CsBr / chlorobenzene solution obtained in step (2) to 4 mL of the PMMA / chlorobenzene solution obtained in step (1), place the mixed solution on a heating plate, adjust the heating plate temperature to 120°C, the rotation speed to 1600 rpm, and heat and stir for 8 h. Then add 200 μL of the PbBr2 / chlorobenzene solution obtained in step (2), continue heating and stirring at 120°C and 1600 rpm for 10 h, and obtain a CsPbBr3 / chlorobenzene solution.
[0070] The images of the CsPbBr3 quantum dot precursor solution prepared in Example 1-4 under white light and 365nm ultraviolet light are shown in Figure 3 .
[0071] Example 5
[0072] Coupling Growth of CsPbBr3 Quantum Dots and Sapphire
[0073] After preheating the CsPbBr3 solution prepared in Example 1 to 80°C, 200 μL of the CsPbBr3 solution was added dropwise to the cleaned 1.5×1.5 cm 2 The CsPbBr3 / PMMA wet film was obtained by spin coating at 2000 rpm for 30 seconds using a coating machine. The obtained CsPbBr3 / PMMA wet film substrate was placed on a heating plate at 80°C to promote the in-situ nucleation and crystallization of CsPbBr3 perovskite quantum dots. Annealing was performed at 80°C for 3 minutes to obtain a CsPbBr3 / PMMA quantum dot composite film that was in-situ grown and coupled on a sapphire wafer.
[0074] The images of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the sapphire wafer in Example 5 under white light and 365nm ultraviolet light are shown in FIG. Figure 4 .
[0075] Example 6
[0076] Coupling Growth of CsPbBr3 Quantum Dots and Silicon Wafers
[0077] After preheating the CsPbBr3 solution prepared in Example 1 to 70°C, 200 μL of the CsPbBr3 solution was added dropwise to the cleaned 1.5×1.5 cm 2 On a silicon substrate. Use a coating machine to spin coat at 2000 rpm for 20 seconds to obtain a CsPbBr3 / PMMA wet film. Place the obtained CsPbBr3 / PMMA wet film substrate on a 60°C heating plate to promote in-situ nucleation and crystallization of CsPbBr3 perovskite quantum dots. Anneal at 60°C for 3 minutes to obtain a CsPbBr3 / PMMA quantum dot composite film that is in-situ grown and coupled on a silicon wafer.
[0078] The images of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the silicon wafer in Example 6 under white light and 365nm ultraviolet light are shown in Figure 5 .
[0079] Example 7
[0080] Coupling Growth of CsPbBr3 Quantum Dots and Silicon Carbide
[0081] After preheating the CsPbBr3 solution prepared in Example 1 to 80°C, 200 μL of the CsPbBr3 solution was added dropwise to the cleaned 1×1 cm 2 On a silicon carbide substrate. Use a coating machine to spin coat at 2000 rpm for 25 seconds to obtain a CsPbBr3 / PMMA wet film. Place the obtained CsPbBr3 / PMMA wet film substrate on a 110°C heating plate to promote in-situ nucleation and crystallization of CsPbBr3 perovskite quantum dots. Anneal at 110°C for 4 minutes to obtain a CsPbBr3 / PMMA quantum dot composite film that is in-situ grown and coupled on a silicon carbide wafer.
[0082] The images of the in-situ grown coupled CsPbBr3 / PMMA quantum dot composite film on the silicon carbide wafer in Example 7 under white light and 365nm ultraviolet light are shown in Figure 6 .
[0083] Example 8
[0084] Coupling Growth of CsPbBr3 Quantum Dots and Silicon Dioxide
[0085] After preheating the CsPbBr3 solution prepared in Example 1 to 90°C, 200 μL of the CsPbBr3 solution was added dropwise to the cleaned 1.5×1.5 cm 2 On a silicon dioxide substrate. Use a coating machine to spin coat at 2000 rpm for 20 seconds to obtain a CsPbBr3 / PMMA wet film. Place the obtained CsPbBr3 / PMMA wet film substrate on a 90°C heating plate to promote in-situ nucleation and crystallization of CsPbBr3 perovskite quantum dots. Anneal at 90°C for 1 minute to obtain a CsPbBr3 / PMMA quantum dot composite film that is in-situ grown and coupled on a silicon dioxide wafer.
[0086] The images of the CsPbBr3 / PMMA quantum dot composite film in situ grown on the silicon dioxide wafer under white light and 365nm ultraviolet light are shown in Example 8. Figure 7 .
[0087] Figure 8 These are SEM images of the coupling of CsPbBr3 quantum dots and silicon carbide wafers in Example 7, wherein (a) is the wetting effect of CsPbBr3 quantum dots in micron-scale defects, and (b) is the wetting effect of CsPbBr3 quantum dots in nanometer-scale defects.
[0088] from Figure 8 It can be clearly observed that the distribution and coupling of CsPbBr3 quantum dots in different types of defects further proves its excellent performance in defect detection.
[0089] For micron-sized surface defects, CsPbBr3 quantum dots can couple well to the defect area and form uniform markings inside and around the defect. This shows that CsPbBr3 quantum dots have excellent dispersion and adhesion, and can effectively cover and mark larger defect areas. Figure 8 (a) shows the distribution of CsPbBr3 quantum dots in micron-scale defects. The image shows that the quantum dots are evenly distributed inside the defect, with a significant marking effect, and can clearly depict the morphology and contour of the defect.
[0090] For tiny nano-scale defects, CsPbBr3 quantum dots show more significant advantages. Its solution can penetrate deep into the nano-scale defects, achieving a greater depth infiltration effect. In particular, CsPbBr3 quantum dots can extend along the depth direction of the defect, forming a mark with a depth far greater than the width, and the depth ratio can reach 1:3. Figure 8 (b) shows the wetting effect of CsPbBr3 quantum dots in nanoscale defects. The image shows that quantum dots can not only cover the surface of the defect, but also penetrate into the defect to form a clear depth mark. This deep marking capability significantly enhances the accuracy and effectiveness of defect detection.
[0091] Fig. 9 This is a diagram showing the effect of CsPbBr3 quantum dots on silicon dioxide wafer defect detection in Example 8.
[0092] Defect fluorescent marking effect: Fig. 9 It can be seen that the lens coupled with CsPbBr3 quantum dots shows obvious fluorescence signals under ultraviolet light. Quantum dots can effectively mark pits and other tiny defects on the surface of the lens, which are difficult to detect under ordinary white light microscope.
[0093] Pit mark: For the pits on the lens surface ( Fig. 9 The CsPbBr3 quantum dots can penetrate deep into the pit and are evenly distributed in the defect area. This makes the pit show a significant fluorescence signal under ultraviolet light, clearly depicting the shape and depth of the pit.
[0094] Small defect marking: In addition, CsPbBr3 quantum dots can also mark small defects that are not obvious under white light microscopy ( Fig. 9 The part marked in the blue box in the middle). The lateral resolution can reach 214nm and the axial resolution is 1010nm. Under the irradiation of ultraviolet light, these tiny defects show obvious fluorescent signals due to the high fluorescence efficiency of quantum dots, thus achieving accurate defect detection.
[0095] Example 9
[0096] Synthesis of FAPbI3 / DMF quantum dot solution and coupled growth of FAPbI3 / DMF quantum dots and silica
[0097] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of DMF were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 90°C, the speed was adjusted to 1600 rpm, and the mixture was heated and stirred for 1 h until a transparent solution was formed, i.e., PMMA / DMF solution.
[0098] (2) In a glove box with a nitrogen environment, take 1.712g FAI and 0.461g PbI2 powder into a 40mL glass bottle, add 5mL DMF to each, and put in a magnet. Place the above two solutions on a heating plate, set the heating temperature to 60°C, set the speed to 1300rpm, and stir overnight. Then filter the above two solutions through a 0.22μm syringe filter to obtain FAI / DMF solution and PbI2 / DMF solution, respectively.
[0099] (3) Add 300 μL of the FAI / DMF solution obtained in step (2) to 4 mL of the PMMA / DMF solution obtained in step (1), place the mixed solution on a hot plate, adjust the temperature of the hot plate to 100°C, the speed to 1600 rpm, and heat and stir for 10 hours. Then add 300 μL of the PbI2 / DMF solution obtained in step (2), continue heating and stirring at 100°C and 1600 rpm for 10 hours, and obtain a FAPbI3 / DMF solution.
[0100] (4) After preheating the prepared FAPbI3 / DMF solution to 100°C, 200 μL of FAPbI3 solution was added dropwise to the cleaned 1.5×1.5 cm 2 On a silicon dioxide substrate. Use a coating machine to spin coat at 2000 rpm for 20 seconds to obtain a FAPbI3 / PMMA wet film. Place the obtained FAPbI3 / PMMA wet film substrate on a 100°C heating plate to promote in-situ nucleation and crystallization of FAPbI3 perovskite quantum dots. Anneal at 100°C for 1 minute to obtain an in-situ growth-coupled FAPbI3 / PMMA quantum dot composite film on a silicon dioxide wafer.
[0101] The images of the FAPbI3 / PMMA quantum dot composite film in situ grown on the silicon dioxide wafer in Example 9 under white light and 365nm ultraviolet light are shown in Fig.10 .
[0102] Example 10
[0103] Synthesis of CsPbI3 / DMF quantum dot solution and coupled growth of CsPbI3 / DMF quantum dots and silica
[0104] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of DMF were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 90°C, the speed was adjusted to 1600 rpm, and the mixture was heated and stirred for 1 h until a transparent solution was formed, i.e., PMMA / DMF solution.
[0105] (2) In a glove box with a nitrogen environment, take 0.259g CsI and 0.461g PbI2 powders into a 40mL glass bottle, add 5mL DMF to each, and place a magnet. Place the two solutions on a heating plate, set the heating temperature to 60°C, set the speed to 1300rpm, and stir overnight. Then filter the two solutions through a 0.22μm syringe filter to obtain FAI / DMF solution and PbI2 / DMF solution, respectively.
[0106] (3) Add 300 μL of the CsI / DMF solution obtained in step (2) to 4 mL of the PMMA / DMF solution obtained in step (1), place the mixed solution on a heating plate, adjust the heating plate temperature to 90°C, the rotation speed to 1600 rpm, and heat and stir for 10 h. Then add 300 μL of the PbI2 / DMF solution obtained in step (2), continue heating and stirring at 90°C and 1600 rpm for 10 h, and obtain a CsPbI3 / DMF solution.
[0107] (4) After preheating the prepared CsPbI3 solution to 90°C, 200 μL of CsPbI3 solution was added dropwise to the cleaned 1.5×1.5 cm 2 On a silicon dioxide substrate. Use a coating machine to spin coat at 2000 rpm for 20 seconds to obtain a CsPbI3 / PMMA wet film. Place the obtained CsPbI3 / PMMA wet film substrate on a 90°C heating plate to promote in-situ nucleation and crystallization of CsPbI3 perovskite quantum dots. Anneal at 90°C for 1 minute to obtain a CsPbI3 / PMMA quantum dot composite film that is in-situ grown and coupled on a silicon dioxide wafer.
[0108] The images of the CsPbI3 / PMMA quantum dot composite film in situ grown on the silicon dioxide wafer in Example 10 under white light and 365nm ultraviolet light are shown in Fig.11 .
[0109] Embodiment 11
[0110] Synthesis of Cs3Cu2I5 / DMF Quantum Dots Solution and Coupling Growth of Cs3Cu2I5 / DMF Quantum Dots and Silica
[0111] (1) In a glove box with a nitrogen atmosphere, 1 g of PMMA and 4 mL of DMF were mixed and placed in a magnetic bar. The mixed solution was placed on a hot plate, the temperature of the hot plate was set to 90°C, the speed was adjusted to 1600 rpm, and the mixture was heated and stirred for 1 h until a transparent solution was formed, i.e., PMMA / DMF solution.
[0112] (2) In a glove box with a nitrogen environment, take 0.259 g of CsI and 0.190 g of CuI powder into a 40 mL glass bottle, add 5 mL of DMF to each, and place a magnetic particle. Place the two solutions on a heating plate, set the heating temperature to 60°C, set the speed to 1300 rpm, and stir overnight. Then filter the two solutions through a 0.22 μm syringe filter to obtain CsI / DMF solution and CuI / DMF solution, respectively.
[0113] (3) Add 300 μL of the CuI / DMF solution obtained in step (2) to 4 mL of the PMMA / DMF solution obtained in step (1), place the mixed solution on a heating plate, adjust the heating plate temperature to 80°C, the rotation speed to 1600 rpm, and heat and stir for 10 h. Then add 200 μL of the CsI / DMF solution obtained in step (2), continue heating and stirring at 80°C and 1600 rpm for 10 h, and obtain a Cs3Cu2I5 / DMF solution.
[0114] (4) After preheating the prepared Cs3Cu2I5 solution to 80°C, 200 μL of Cs3Cu2I5 solution was added dropwise to the cleaned 1.5×1.5 cm 2 On a silicon dioxide substrate. Use a coating machine to spin coat at 2000 rpm for 20 seconds to obtain a Cs3Cu2I5 / PMMA wet film. Place the obtained Cs3Cu2I5 / PMMA wet film substrate on a heating plate at 80°C to promote the in-situ nucleation and crystallization of Cs3Cu2I5 perovskite quantum dots. Anneal at 80°C for 1 minute to obtain a Cs3Cu2I5 / PMMA quantum dot composite film that is in-situ grown and coupled on a silicon dioxide wafer.
[0115] The images of the Cs3Cu2I5 / PMMA quantum dot composite film in situ grown on the silicon dioxide wafer under white light and 245nm ultraviolet light are shown in Example 11. Fig.12 .
[0116] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for detecting defects in an optoelectronic wafer, characterized in that: The following steps are involved: The quantum dot precursor solution is coated on the surface of the optoelectronic wafer and annealed. After the quantum dot film is formed, it is irradiated under ultraviolet light. The displayed fluorescent signal can mark the defects on the surface of the optoelectronic wafer, thereby achieving the purpose of detecting defects in the optoelectronic wafer.
2. The method for detecting defects in optoelectronic wafers according to claim 1, characterized in that: The quantum dots include CsPbBr3 quantum dots, FAPbI3 quantum dots, CsPbI3 quantum dots or Cs3Cu2I5 quantum dots.
3. The method for detecting defects in optoelectronic wafers according to claim 1, characterized in that: The material of the optoelectronic wafer includes sapphire, silicon carbide, silicon dioxide, fused quartz, gallium nitride, gallium arsenide or single crystal silicon.
Citation Information
Patent Citations
Method for detecting pinhole defects on passivation layer of semiconductor wafer
CN111341683A
In-situ growth perovskite quantum dot film, preparation method thereof and application of in-situ growth perovskite quantum dot film in fluorescent nondestructive testing
CN118222274A
Cited By
Efficiency-matched quantum dot nanolayer removal method and in-situ growth method and application thereof
CN121006118A
Quantum dot nanolayers with removal efficiency matching, their in-situ growth methods and applications
CN121006118B